A Rare Case of Hodgkin Lymphoma With Isolated Epitrochlear Lymphadenopathy. Our Experience and Main Differential Diagnosis - Laura Cea; Domiziana Santucci; Caterina Bernetti; Lorenzo Nibid; Valeria Tomarchio; Amalia Bruno; Bruno Beomonte Zobel; Rosario Francesco Grasso; Eliodoro Faiella (Case Reports in Medicine)
Hodgkin lymphoma (HL) is a type of lymphoma, characterized by the presence of abnormal Reed-Sternberg cells. It typically affects lymph nodes, generally in the upper body (such as neck, chest, and armpits). It can also involve the spleen, liver, and bone marrow. In the literature, there are sporadic cases of atypical localization of HL. The aim of this article is to report a peculiar case of HL in a 55-year-old male presenting with primary epitrochlear lymphadenopathy as the only localization of disease, also performing a literature review on this atypical presentation. We also summarized the possible underlying malignant pathologies that arise from the soft tissues of the upper limb adjacent to the elbow.